P028 Do we really need to send an MSU?. (30th June 2016) - Rooke, Bethanie; Baker, Alice; Barrett, Sarah
Abstract : Background/introduction: Midstream urine (MSU) results create a significant workload for our clinic. MSU can diagnose urinary tract infection (UTI), but detecting asymptomatic bacteriuria or contaminants confuses management. Lower UTI is common in non-pregnant women, but MSU is unnecessary as UTI can be diagnosed clinically. Local guidelines identified four indications for MSU: women with dysuria and loin pain, urinary symptoms in pregnancy, men with dysuria and frequency/urgency, and epididymo-orchitis. Aim(s)/objectives: To assess whether MSU is requested for appropriate indications, and to evaluate the usefulness of MSU in diagnosing and managing patients in a sexual health clinic. Methods: Retrospective case note review of 100 MSU requests at a sexual health clinic between 2014 and 2015. The associated clinical presentations and culture results were identified. Results: 14% of MSU were requested within guidelines. 29% (4/14) of those were positive, compared to 22% (19/86) not requested within guidelines. Indications outside guidelines associated with positive culture included: women with lower urinary tract symptoms (11), men with dysuria only (3), pelvic inflammatory disease (2), asymptomatic with positive urine dipstick (2), and vaginal discharge (1). 15/23 were sensitive and 8/23 were resistant to trimethoprim. Discussion/conclusion: MSU is often requested inappropriately.This generates positive results associated with clinical presentations unlikely to indicate UTI. Greater awareness amongst clinicians of appropriate indications for MSU will support optimal resource utilisation in sexual health clinics. Resistance to our first line antibiotic, trimethoprim, was identified. Resistance patterns should be monitored so clinicians can confidently prescribe empirical treatment for lower UTI in non-pregnant women.